2023
DOI: 10.1002/mog2.25
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids in cancer: Metabolic functions and potential treatment

Abstract: Lipid metabolic reprogramming is one of the important metabolic characteristics of cancer cells. As major components of lipids, fatty acids provide energy and material basis for cancer cell survival. Abnormal fatty acid metabolism has been found in many cancers. Fatty acid uptake, transport, and synthesis are closely related to the pathogenesis of cancer. Meanwhile, fatty acid changes in the membrane structure of cancer cells and signal transduction mediated by signaling lipids are also helping cancer cells su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 212 publications
(553 reference statements)
0
6
0
Order By: Relevance
“…44 As well, alterations of FA metabolism contribute to cellular proliferation, epithelial-mesenchymal transition, migration, and invasion. 45 The de novo synthesis of saturated polysaccharides that contribute to cell membrane structure in tumorigenesis also allows for cells to become more resistant to oxidative stress caused by chemotherapy. 44 Cholesterol has been considered a high-risk factor and prognostic indicator.…”
Section: Fa and Cholesterolmentioning
confidence: 99%
See 4 more Smart Citations
“…44 As well, alterations of FA metabolism contribute to cellular proliferation, epithelial-mesenchymal transition, migration, and invasion. 45 The de novo synthesis of saturated polysaccharides that contribute to cell membrane structure in tumorigenesis also allows for cells to become more resistant to oxidative stress caused by chemotherapy. 44 Cholesterol has been considered a high-risk factor and prognostic indicator.…”
Section: Fa and Cholesterolmentioning
confidence: 99%
“…107 Other studies have also identified increased lipids in the cell membranes to be associated with radiotherapy and chemotherapy resistance. 45 Furthermore, blocking de novo FA synthesis may increase cancer cell sensitivity. 45 Targeting FA synthesis as an anticancer therapeutic has been speculated to be promising, however, the translation of this clinic has been Abbreviations: ADI-PEG, pegylated arginine deiminase; CTLA4, cytotoxic T-lymphocyte-associated protein 4; IGF1, insulin-like growth factor-1; MDSC, myeloid-derived suppressor cell; NSCLC, non-small cell lung cancer; pCR, pathologic complete response; PD-1/PD-L1, programmed cell death protein 1/programmed cell death ligand 1; TIL, tumor infiltrating lymphocyte; TME, tumor microenvironment.…”
Section: Fa Synthesismentioning
confidence: 99%
See 3 more Smart Citations